Problematika Perpecahan Organisasi Advokat: Problematika Perpecahan Organisasi Advokat - Helvis Helvis; Iqbal Subhan Nugraha (Dame Journal of Law, 2025)
The advocate profession has a central role in the legal system as a guardian of justice and a protector of human rights. However, the integrity of this profession faces serious challenges due to the division of advocate organizations in Indonesia. This phenomenon is triggered by various factors, such as differences in internal and external interests, power dynamics, and disagreements regarding ethical standards and professionalism. Organizational fragmentation not only weakens the position of advocates as a collective entity, but also negatively impacts the effectiveness of the justice system and public trust. This article aims to examine the root causes of these divisions and offer strategic solutions to strengthen the unity and professionalism of advocacy organizations. With an analytical and reflective approach, this research is expected to contribute to the reconstruction of advocate institutions that are more inclusive and equitable in Indonesia.